PERAN BUDAYA ORGANISASI DAN KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN - Isnah Karimah; Siti Nurhayati (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2023)
The purpose of this research is to determine the influence organizational culture and leadership on employee performance. The type of this research is explanatory research with a quantitative approach. The sample in this study consists of 30 employee at Khenzo S & R. Data collection techniques use the survey method by distributing questionnaires. Data analysis uses the multiple linear regression method. The result of the analysis shows that organizational culture has a significant positive effect on employee performance. Leadership has a significant positive effect on employee performance. Organizational culture and leadership have a significant positive effect on employee performance. The adjusted R square value is 0.636 shows that organizational culture and leadership have an effect of 63.6% on employee performance and the rest 36.4% is influenced by other variables not included in this study. The other variable that can be add for the future research are compensation, motivation, commitment, employee satisfaction and work environment.